The potential antifeedant activity of lichen-forming fungal extracts against the invasive Spanish slug ( Arion vulgaris) - Zolovs, Maksims; Jakubāne, Iveta; Kirilova, Jelena; Kivleniece, Inese; Moisejevs, Rolands; Koļesnikova, Jelena; Pilāte, Digna (Canadian Journal of Zoology, 2020)
The protection of horticultural crops from slug feeding can be achieved using slug pellets; however, application of molluscicides is not always safe for the environment. There is a need for alternative methods to reduce the palatability of crop plants. Chemical properties of secondary compounds from lichens influence the feeding behaviour of slugs. Liquid extracts of three lichen species (Cladonia rangiferina (L.) F.H. Wigg., Cladonia stellaris (Opiz) Pouzar & Vězda, and Pseudevernia furfuracea (L.) Zopf) were applied to three different crops and tested for their antifeedant properties against an important agricultural pest, the Spanish slug (Arion vulgaris Moquin-Tandon, 1855). All three extracts had specific activity, showing a decrease in grazing intensity as well as slug mass loss after feeding on treated food. Slugs significantly gained mass after feeding under control condition; however, they did not gain mass when fed on extract-treated food. The most effective extract was from P. furfuracea. We propose to use properties of lichen extracts to develop new environmentally friendly molluscicides.